Business resiliency and its effect on the relationship of uncertainties and business continuity: The case of food MSMEs in Santa Rosa, Laguna - Bacierto, Marcky Frank J. (Animo Repository, 2022)
Uncertainties are events that adversely affects the continuity of a business; various literature suggest that the concept of business resilience functions as a mediator between the two in order to mitigate the effects of the former on the latter. The primary objective of the study is to confirm the aforementioned mediating effect of business resilience on the relationship of uncertainties and business continuity through mediation analysis. Furthermore, the study aims to: evaluate the extent of each aforementioned on the food MSMEs of Santa Rosa, Laguna through descriptive analytics; determine the relationship of uncertainties with business resilience and business continuity and the relationship of business resilience and business continuity through correlational analysis; and identify the effects of uncertainties on business resilience and business continuity and the effect of business resilience and business continuity through regression analysis. The findings of study were substantive and contributes new knowledge on business research. The results of the study indicate that the only effect and relationship present is between the variables business resilience and business continuity. The presumed effects and relationship of uncertainties with business resilience and business continuity were identified to be not significant because it was determined by the researchers that as either business resilience or business continuity increases, the lesser of a threat uncertainties become; and since the relationship between uncertainties and business continuity are not significant, then the mediation of business resilience is no longer necessary.